Day surgery: development of a national comparative audit service. Issue 3 (September 1993) - Black, N; Petticrew, M; Hunter, D; Sanderson, C
Abstract : OBJECTIVES–To develop software for hospitals to analyse their own survey data on patients' experiences of day surgery and to create and test the feasibility of a national comparative audit service. DESIGN–Software development and testing; database analysis. SETTING–Eleven general hospitals in England. PATIENTS–1741 day surgery patients undergoing procedures during 1991-2. MAIN MEASURES–Postoperative symptoms, complications, health and functional status, general satisfaction, and satisfaction with specific aspects of care. RESULTS–Software for data entry and analysis by hospitals was successfully used at the pilot sites. The overall response rate for the 11 hospitals using the questionnaire was 60%, ranging from 33% to 90% depending on the way the survey was managed. Data from all 11 hospitals were included in the national comparative audit database. Hospitals showed little variation in measures of patients' overall satisfaction (around 85%), but significant differences were apparent for specific aspects such as receiving adequate written information before admission (range 50%-89%), provision of adequate parking facilities (14%-92%) and experiencing a significant amount of postoperative pain (8%-42%). The proportion of day case patients undergoing procedures that could have been performed in outpatient departments varied from 0 to 27% between hospitals. Further comparisons of outcome, in particular measures of effectiveness, must await the development of validated case mix adjustment methods. CONCLUSION–Establishing a comparative audit database is feasible but several methodological problems remain to be resolved.